A comparative study between single dose intralesional autologous blood and corticosteroid injection in chronic plantar fasciitis-a short term follow-up study - N. B., Mahesh Kumar; T. S., Deepanand (International Journal of Research in Medical Sciences, 2023)
Background: Plantar fasciitis was initially thought to be an acute inflammatory disease, but histology findings show that it is a chronic degenerative process leading to pain at the calcaneal insertion without any inflammation. The diagnosis of plantar fasciitis is mainly based on clinical symptoms, like heel pain and tightness, and diagnostic imaging is not routinely required. Injection of autologous blood can help stimulate a healing response in chronic tendon disorders. Methods: Radiological imaging of the affected foot in lateral view will be taken. 30 patients will be treated with 2 ml of autologous blood with 1 ml lidocaine and another 30 patients with 2 ml of triamcinolone acetonide with 1 ml lidocaine. The main outcomes measured are subjective based on the visual analog scale done pre-injection, 2 weeks, 4 weeks and 12 weeks post injection. Final outcome was measured based on the pain and activity level at 3 months. Results: The corticosteroid group showed an early sharp and then more gradual improvement in pain scores, but autologous blood group had a steady gradual drop in pain. Conclusions: Autologous whole blood and corticosteroid local injection can both be considered as effective methods in the treatment of chronic plantar fasciitis.